2018
DOI: 10.1111/jvim.15335
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of toceranib phosphate (Palladia®) use in the treatment of gastrointestinal stromal tumors of dogs

Abstract: BackgroundGastrointestinal stromal tumors (GISTs) are uncommon intestinal neoplasms in the dog. Literature regarding adjunctive therapy for GISTs in dogs is sparse. High‐risk GISTs in humans respond to tyrosine kinase inhibition in the adjuvant setting.ObjectivesTo review cases of toceranib phosphate use in dogs with GISTs and provide initial assessment of possible biological activity. A secondary aim was to evaluate patient and tumor characteristics for possible prognostic value.AnimalsTwenty‐seven dogs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
82
2
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(120 citation statements)
references
References 38 publications
9
82
2
10
Order By: Relevance
“…Toceranib is a multitargeted TKI targeting several RTKs, including VEGFR, PDGFR, KIT, CSF1R, and FLT3 and was developed as an orally bioavailable anti‐angiogenic drug . While it was approved for the treatment of canine mast cell tumours owing to its KIT inhibitory properties, toceranib has demonstrated activity against other solid histologies, including sarcomas and carcinomas . Its clinical utility remains unclear based on several recent studies.…”
Section: Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Toceranib is a multitargeted TKI targeting several RTKs, including VEGFR, PDGFR, KIT, CSF1R, and FLT3 and was developed as an orally bioavailable anti‐angiogenic drug . While it was approved for the treatment of canine mast cell tumours owing to its KIT inhibitory properties, toceranib has demonstrated activity against other solid histologies, including sarcomas and carcinomas . Its clinical utility remains unclear based on several recent studies.…”
Section: Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Its clinical utility remains unclear based on several recent studies. A recent retrospective evaluation of dogs with GISTs treated with toceranib documented objective response (complete or partial response) in 4/7 dogs with measurable disease, suggesting efficacy in this specific tumour type . However, other studies have failed to show a clear clinical benefit.…”
Section: Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent report from the National Academy of Medicine (64), only one out of ten oncology candidates that appear promising in preclinical mouse models are in fact effective and safe in human clinical trials. This overtly high attrition rate highlights the need for alternative models at the early stage of the Drug Research and Development lifecycle (65), as shown in other therapeutic areas (66)(67)(68)(69)(70)(71).…”
Section: Comparative Oncology: An Opportunity To Accelerate Parallel mentioning
confidence: 99%